Thoracic Chordoma of Thoracal 7th - 8th: A Case Report (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2019)
Abstract: Spinal chordomas are rare, locally invasive, malignant neoplasm, representing 5% of all malignant tumors of the skeleton. This publication is based on a case of a thoracal chordoma in a 53 year old man at Haji Adam Malik General Hospital Medan. Patient with a major complaint of back pain accompanied by weakness in both lower limbs, beginning with numbness and tingling sensation. Based on physical examination, thoracal CT-Scan and Thoracal MRI, diagnosis of a thoracal chordoma was made. Laboratory was normal. There was no other comorbidities. Surgical treatment was applied in this case. The patient performed laminectomy tumor removal on throracal 7th-8th, followed with posterior stabilization on thoracal 5th-6th and thoracal 9th-10th. We managed to achieve near complete macroscopic tumor resection in this case. Tumor samples were taken for Histopathologhy analysis. From the microscopy finding we found a typical cell of a chordoma.On the 7th day the patient was discharged. The patient then controls for follow up and radiotherapy. Patient neurologically improved, no complications and no surgical implants failures in this case. After surgery, the patient underwent radiotherapy. The main goal of therapy in this chordoma case is total eradication, spinal decompression without neurologic impairment and prevention of recurrence.